Mothers’ Knowledge on Motor Development Stimulation in Toddlers at Puskesmas Kota Utara - Djafar, Oktaviani; Mohamad, Rini Wahyuni; Rahma, Sitti (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Toddler age is considered part of the golden age, a crucial period for achieving optimal intellectual growth and development. During this stage, the rate of physical growth begins to slow, while motor development progresses significantly. Parental knowledge regarding developmental stimulation can influence the effectiveness of such stimulation. The purpose of this study was to describe mothers’ knowledge of motor development stimulation in toddler-aged children within the working area of Puskesmas Kota Utara. This research employed a quantitative method with a descriptive research design. The study population consisted of mothers with toddler-aged children. A total of 115 respondents were selected using a total sampling technique. The results showed that 73 respondents (63.5%) had a low level of knowledge, while 42 respondents (36.5%) demonstrated a good level of knowledge regarding motor development stimulation. It can be concluded that most mothers had limited knowledge, indicating the need for health professionals at the Public Health Center to provide health promotion interventions through educational activities aimed at improving maternal understanding of motor development stimulation.